2018
DOI: 10.1016/j.jenvman.2017.10.062
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between system performance and bacterial composition under varied mixing intensity in thermophilic anaerobic digestion of food waste

Abstract: This study examines the stability and efficiency of thermophilic anaerobic digesters treating food waste under various mixing velocities (50-160 rpm). The results showed that high velocities (120 and 160 rpm) were harmful to the digestion process with 18-30% reduction in methane generation and 1.8 to 3.8 times increase in volatile fatty acids (VFA) concentrations, compared to mild mixing (50 and 80 rpm). Also, the removal rate of soluble COD dropped from 75 to 85% (at 50-80 rpm) to 20-59% (at 120-160 rpm). Sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“…These species produced hydrogen from cellulose, and further hydrogenotrophic methanogens are required to convert hydrogen to methane, but they were not found in sufficient quantity in agitated digesters, and a retardation of methane production was noted. Similar results were obtained by Ghanimeh et al [18] in which the Petrotoga genus (phylum of Thermotogae) proliferated under mixing conditions, whereas in non-mixed digesters its absence was noted. It was also stated that the genus Petrotoga played an important role in the degradation of organic matter.…”
Section: Effect Of Mixing On the Microbial Communitysupporting
confidence: 89%
See 3 more Smart Citations
“…These species produced hydrogen from cellulose, and further hydrogenotrophic methanogens are required to convert hydrogen to methane, but they were not found in sufficient quantity in agitated digesters, and a retardation of methane production was noted. Similar results were obtained by Ghanimeh et al [18] in which the Petrotoga genus (phylum of Thermotogae) proliferated under mixing conditions, whereas in non-mixed digesters its absence was noted. It was also stated that the genus Petrotoga played an important role in the degradation of organic matter.…”
Section: Effect Of Mixing On the Microbial Communitysupporting
confidence: 89%
“…Ghanimeh et al [18] carried out microbial analysis at various mixing speeds ranging between 80 and 160 rpm. It has been observed that the agitated digester was dominated by Thermotogae phylum (89% at 80 rpm, 87% at 50 rpm and 85% at 160 rpm), which was gradually replaced by Synergistetes.…”
Section: Effect Of Mixing On the Microbial Communitymentioning
confidence: 99%
See 2 more Smart Citations
“…Stepwise feeding mode without dilution had a lower performance and instability because of insufficient contact between substrate and microorganisms and decrease of effective volume. Ghanimeh et al [6] put the research on varied mixing intensity strategy in thermophilic FW anaerobic digestion. They found that high mixing velocities (120 and 160 rpm) were harmful to the digestion process with 18-30% reduction in methane yield and 1.8 to 3.8 times increase in VFA concentrations which has inhibitive effect on AD process when VFA content is overmuch.…”
Section: Operational Alternationmentioning
confidence: 99%